2016
DOI: 10.1186/s12876-016-0433-4
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholic vs non-alcoholic fatty liver in rats: distinct differences in endocytosis and vesicle trafficking despite similar pathology

Abstract: BackgroundNon-alcoholic and alcoholic fatty liver disease (NAFLD and AFLD, respectively) are major health problems, as patients with either condition can progress to hepatitis, fibrosis, and cirrhosis. Although histologically similar, key differences likely exist in these two models. For example, altered content of several vesicle trafficking proteins have been identified in AFLD, but their content in NAFLD is unknown. In this study, we compared select parameters in NAFLD and AFLD in a rat model.MethodsWe fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 53 publications
3
27
0
Order By: Relevance
“…Serum total bile acid concentrations were markedly elevated by sevenfold from 1.9 ± 1.0 μM in wt control mice to 14.9 ± 5.4 μM in ob/ob mice [118]. In contrast to the findings from the studies described above, a more recent study showed that total serum bile acid concentrations were not significantly different in HFD-induced NAFLD mice than mice on control diet [119].…”
Section: Altered Bile Acid Profiles In Nafld Animal Modelsmentioning
confidence: 61%
“…Serum total bile acid concentrations were markedly elevated by sevenfold from 1.9 ± 1.0 μM in wt control mice to 14.9 ± 5.4 μM in ob/ob mice [118]. In contrast to the findings from the studies described above, a more recent study showed that total serum bile acid concentrations were not significantly different in HFD-induced NAFLD mice than mice on control diet [119].…”
Section: Altered Bile Acid Profiles In Nafld Animal Modelsmentioning
confidence: 61%
“…Like NAFLD, the prevalence of AFLD is expected to rise (Toshikuni et al 2014). While both AFLD and NAFLD have similar histology and disease progression, AFLD also induces molecular and clinical changes that are attributed to high alcohol consumption, and not as a result of hepatic lipid accumulation (Toshikuni et al 2014, Rasineni et al 2016. Interestingly, both AFLD and NAFLD are strongly associated with metabolic syndrome and type 2 diabetes (Kotronen et al 2010), suggesting that fatty liver, independent of origin, promotes systemic metabolic dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…For the NAFLD model, simple steatosis was generated by feeding 200 g male Wistar rats with a high-fat diet consisting of 60% calories from saturated, monounsaturated, and polyunsaturated fatty acids (ResearchDiets, D08060104) ad libitum for 8 weeks. 5 To generate their respective controls, rats of the same age and weight were fed a control diet consisting of 10% calories from fatty acids (Research Diets, D12450K) ad libitum for 8 weeks. For the AFLD model, male Wistar rats were pair-fed with Lieber− DeCarli control or EtOH−liquid diets that contained calories of 18% from protein, 35% from fat, 11% from carbohydrate, and 36% from ethanol.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…For the AFLD model, male Wistar rats were pair-fed with Lieber− DeCarli control or EtOH−liquid diets that contained calories of 18% from protein, 35% from fat, 11% from carbohydrate, and 36% from ethanol. 5 In the control diet, ethanol was replaced isocalorically with maltodextrin.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%